Érico Gobbi: resgatando a memória de um escultor riograndino - Lopes, Leda Cristina Peres (2018)
The aim of this present research work is based on making an inventory of part of the works collection of a riograndino sculptor, called Erico Gobbi. There are approximately more than hundred collections of works and they are available on his atelier entitled Erico Gobbi Sculptor Art Works Gallery (GAEEG) and on the public places in Rio Grande city, his hometown. This prospect showed that there is no identification on a huge quantity of his works, especially those ones that are presented on his atelier and his art gallery. Therefore, it was noticed that there is a necessity of retrieving and recording such relevant information from each sculpture. In spite of the fact that there is a wide sculptural collection for cataloging and filling the inventory form, the items exhibited at OAEEG space and those ones localized at GAEEG were investigated. Besides that, it was highlighted in a photographic catalog, as an illustration of the current study, the rest of the available works at the art gallery. In addition to that, trough this documentary investigation, a significant information in relation to the artist and his works was collected. This actual examine was also focused on the depositions of Érico Gobbi´s son, Edson, and Érico Gobbi´s widow, lady Ayda, who know each sculpture history. As can be seen from this summary, the artist Érico Gobbi left a cultural heritage to the riograndino people. This discovery intends to study it and divulge it under its cultural aspects, considering it the patrimony and memory of the artist and the city of Rio Grande / RS